Development of a monitoring and control system for operational study of dividing wall column pilot plant - -, -; Yunus, M. Y. M.; Abdul Samad, Noor Asma Fazli; Shafie, Mohammad
Dividing wall column (DWC) provides a good alternative for processes using conventional distillation column due to possible saving in both energy and capital cost. So far, about 40 divided wall columns (DWCs) are in operation worldwide, about 30 of them within the BASF group. The potential of DWC is however and not applied to broad range of the separation processes due to the challenges in design, simulate, operation and control. The internal configuration of DWC leads to changes in the controllability and operating mode thus becoming a potential hurdle for commercial implementation. In this work we perform several studies related to control and operation of DWC. Moreover, DWC exhibits a multiple input multiple output (MIMO) characteristics. For good process control it is important to consider the probability of pairing the controlled variables and manipulated variables and applying an effective feedback controller to each selected pairs. An appropriate controller pairing is important to reject the disturbances as well as maintaining the product specifications. In our knowledge, there are few research focuses of VDWC particularly for oleochemical products fractionation. Therefore, our aim in this work is to analyze the controllability of a VDWC for fractionation of oleochemical fatty acid.